States at the Crossroads: innovation policies and its coordination dilemmas - Mouallem, Pedro Salomon Bezerra (2019)
Discourses and policies on innovation have acquired importance in the development strategies of many countries in recent decades. In this movement, new roles of the State were formulated regarding promotion of innovation, in view of successful experiences in this field. Among these roles is the need for state coordination. This paper aims at articulating researches suggesting that intra-state coordination rise as a central variable to Innovation Policies, and discussing issues of state organization emerging from this agenda. To explore these topics, the paper sheds light on approaches and diagnoses of this literature. Some authors conclude that the coordination activity in this field faces a persistent dynamics of path dependence, as will be discussed from the international experiences. In illuminating arguments and analytical tools of this literature, it is hoped to contribute to this research agenda, not yet fully explored in Brazil.